2015
DOI: 10.1159/000430992
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Reliability of the Chronic Respiratory Disease Questionnaire in Elderly Individuals with Mild to Moderate Non-Cystic Fibrosis Bronchiectasis

Abstract: Background: The chronic respiratory disease questionnaire (CRDQ) is designed to assess health-related quality of life (HRQOL) in chronic respiratory conditions, but its reliability, validity and responsiveness in individuals with mild to moderate non-cystic fibrosis (CF) bronchiectasis are unclear. Objectives: This study aimed to determine measurement properties of the CRDQ in non-CF bronchiectasis. Methods: Participants with non-CF bronchiectasis involved in a randomised controlled trial of exercise training … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…The Chronic Respiratory Disease Questionnaire (CRDQ) consists of 20 items and assesses the domains of dyspnoea, fatigue, emotional function and mastery [113]. It was originally developed for use in COPD and has been validated in both COPD [114] and mild to moderate bronchiectasis [115]. The small study by THOMPSON et al [58] used the CRDQ and reported no health impact for individuals with bronchiectasis who completed 4 weeks of daily ACBT or Flutter.…”
Section: Chronic Respiratory Disease Questionnairementioning
confidence: 99%
“…The Chronic Respiratory Disease Questionnaire (CRDQ) consists of 20 items and assesses the domains of dyspnoea, fatigue, emotional function and mastery [113]. It was originally developed for use in COPD and has been validated in both COPD [114] and mild to moderate bronchiectasis [115]. The small study by THOMPSON et al [58] used the CRDQ and reported no health impact for individuals with bronchiectasis who completed 4 weeks of daily ACBT or Flutter.…”
Section: Chronic Respiratory Disease Questionnairementioning
confidence: 99%
“…Health‐related quality of life (HRQOL) was assessed using the 20‐item Chronic Respiratory Disease Questionnaire (CRQ). The questionnaire consists of dyspnea, fatigue, emotional function, and mastery subscores (Cronbach's α .82), 35 with higher scores indicating better HRQOL. The MCID for CRQ is 0.5 36 …”
Section: Methodsmentioning
confidence: 99%
“…The primary outcome will be change in CRQ dyspnea domain (CRQ-D) from baseline to end intervention. The CRQ-D is a valid measure of HRQoL and is responsive to change with pulmonary rehabilitation in people with chronic respiratory diseases including COPD [ 40 ], bronchiectasis [ 41 ] and ILD [ 42 ].…”
Section: Methodsmentioning
confidence: 99%